Calcaneus, calcaneal tendon and retrocalcaneal bursa. Historical overview and plea for an accurate terminology - Kachlik, D; Musil, V; Vasko, S; Klaue, K; Stingl, J; Baca, V (Acta chirurgica Belgica, 2010)
Diseases and injuries of several specific structures in the heel region have been an enduring focus of medicine: The anatomical terminology of many of these structures has not been established until recently. The aim of the study was a historical analysis of the advances of anatomical terminology of three selected morphological units in the heel region--the Achilles tendon, calcaneus and retrocalcaneal bursa. It starts with a critical evaluation of the mythological eposes, the Illiad and Odyssey, describing the exploits of heroes in the Trojan war, followed by a review of relevant terms used for the designation of selected heel structures in the Middle Ages as well as in the 18" and 19" centuries. Principal versions of Latin anatomical terms used for the denotation of the mentioned structures are discussed. Recently applicable Latin terms and their recommended English synonyms, according to the latest version of Terminologia Anatomica (1998) are summed up. It surveys examples of "not very appropriate" terms, which are frequently used in clinical literature. The authors consider the use of official anatomical terms (both Latin and English) as an important step for the improvement of the clinical expressions and formulations.
Keywords: anatomie; Terminology as Topic; dějiny 16. století; History, Ancient; dějiny 15. století; Mythology; Humans; Portraits as Topic; patní kost; dějiny 18. století; terminologie jako téma; History, 16th Century; mytologie; Calcaneus; Bursa, Synovial; Achillova šlacha; Anatomy; portréty jako téma; Achilles Tendon; History, 18th Century; dějiny 17. století; History, 15th Century; dějiny 20. století; lidé; dějiny starověku; History, 20th Century; History, 17th Century; bursa synovialis